Serum Irisin level is associated with fall risk, muscle strength, and cortical porosity in postmenopausal women - Liang, Hanting; Qi, Wenting; Jiajue, Ruizhi; Chi, Yue; Liu, Wei; Wang, Ou; Li, Mei; Xing, Xiaoping; Yu, Wei; Jiang, Yan; Xia, Weibo (Frontiers in Endocrinology, 2023)
Background: Irisin plays a role in bone-muscle crosstalk, but the relationship between the serum irisin level and bone microarchitecture remains unknown. Objective: This study aimed to investigate the relationships between serum irisin level and fall risk, muscle strength, bone mineral density (BMD), and bone microarchitecture among Chinese postmenopausal women. Methods: In all 138 postmenopausal women, handgrip strength, short physical performance battery (SPPB), and the timed up-and-go test were performed to evaluate muscle strength, physical performance, and fall risk, respectively. The serum irisin was measured. High-resolution peripheral quantitative computed tomography (HR-pQCT) was performed to acquire volumetric BMD and bone microarchitecture. Bivariate analysis was used to explore relationships between serum irisin level and muscle strength and HR-pQCT parameters. Univariate and multivariate linear regression analyses were performed to determine associations between serum irisin level and vBMD and cortical porosity (Ct.Po). Results: All participants had a median serum irisin level of 3.91 μg/ml. Participants with high fall risk had significantly lower serum irisin levels than those with low fall risk (2.22 μg/ml vs. 4.16 μg/ml, p=0.024). Irisin level was positively related to handgrip strength (rs=0.185, p=0.030) and SPPB performance. In univariate linear regression, serum irisin level was positively associated with cortical volumetric BMD (Ct.vBMD, radius: standardized β=0.184, p=0.031; tibia: standardized β=0.242, p=0.004), but it had no significant associations with Ct.vBMD after multivariate adjustment. After adjusting by age, height, serum sclerostin level, and body fat ratio, only Ct.Po at the distal radius had a significantly negative association with serum irisin level (standardized β=-0.276, p=0.003). Conclusion: Postmenopausal women with lower serum irisin levels have a higher fall risk, weaker muscle strength, and higher cortical porosity. Moreover, serum irisin level has a positive association with Ct.vBMD, but it is affected by factors such as age.